(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Nephrotoxicity, with the attendant risk of progression to kidney failure, is a growing problem in many parts of the world. Current orthodox treatment options for nephrotoxicity and kidney failure are limited and there is need for alternative or complementary approaches. This study aimed at evaluating the effect of three structurally related flavonoids, catechin, quercetin and taxifolin on renal redox and metabolite biochemical disturbances in rotenone intoxicated animals. Male Wistar rats were administered 1.5 mg/kg rotenone (s.c.) for ten days followed by post-treatment with catechin (5, 10 or 20 mg/kg), quercetin (5, 10, or 20 mg/kg) and taxifolin (0.25, 0.5 or 1.0 mg/kg) (s.c.), for 3 days. Renal redox indices and levels of renal-related metabolites (creatinine, urea and uric acid) were assessed after sacrifice of animals. Catechin, quercetin and taxifolin significantly attenuated rotenone-induced effects on oxidative stress markers and metabolites linked to renal health. Quercetin was clearly more effective than catechin. The activity demonstrated by taxifolin, despite being administered at the lowest doses, was compelling. The results highlight the potential of these phytochemicals in the management of renal dysfunction. The findings additionally suggest a correlation between the structure of the flavonoids and their activity but also indicate that additional structural considerations beyond conventionally acknowledged ones may be involved.